SATrans: New Free Available Software for Annotation of Transcriptome and Functional Analysis of Differentially Expressed Genes - Zavadil Kokáš, Filip; Bergougnoux, Véronique; Majeská Čudejková, Mária (Journal of computational biology, 2019)
Recent technological advances have made next-generation sequencing (NGS) a popular and financially accessible technique allowing a broad range of analyses to be done simultaneously. A huge amount of newly generated NGS data, however, require advanced software support to help both in analyzing the data and biologically interpreting the results. In this article, we describe SATrans (Software for Annotation of Transcriptome), a software package providing fast and robust functional annotation of novel sequences obtained from transcriptome sequencing. Moreover, it performs advanced gene ontology analysis of differentially expressed genes, thereby helping to interpret biologically-and in a user-friendly form-the quantitative changes in gene expression. The software is freely available and provides the possibility to work with thousands of sequences using a standard personal computer or notebook running on the Linux operating system.
Keywords: Molecular Sequence Annotation; sekvenční analýza RNA; Gene Expression Profiling; transkriptom; Transcriptome; Sequence Analysis, RNA; software; Animals; lidé; Software; stanovení celkové genové exprese; zvířata; Humans; anotace sekvence